Regeneração de tipos de estacas de caule de cajazeira Tratadas com ácido indolbutírico - Rebouças, Kaliane de Oliveira (2011)
Considering the great potential of agro-industrial exploration of Spondias mombin L. and the difficulties in the production of seedlings by cutting this work was carried out in order to evaluate the vegetative propagation of stalk cuttings, with the use de IBA and different cuttings of types. Cuttings were taken from adult plants, healthy nine years old clone cup Lagoa Redonda grafted onto the rootstock of Spondias tuberosa. The experimental design was completely randomized in factorial scheme 3x2, with the following factors: types of cuttings (apical, median and basal) and IBA (0 and 1000 mg. L-1), with five replicates of eight cuttings each, total 240 cuttings. After the treatments, the cuttings were placed for rooting in polyethylene plastic bags containing as substrate a mixture of soil hydromorphic, cattle manure and quartz sand in proportion 1:1:1. Evaluations were performed 165 days after planting, being rated the number of dead cuttings, of dormant cuttings, of buds cuttings active, of cuttings with dormant buds, of cuttings with callus, of cuttings rooted, the number of active buds, of dormant buds, of leaves and leaflets, the leaf dry mass and root, and also, those suitable for planting. It was observed that only for the factor type of cuttings, was significant effect for the following variables: dormant cuttings, cuttings with dormant buds, number of leaves, of leaflets and leaf dry mass and root. The application of IBA or its interaction with different types of cuttings had no effect on the variables. Survival of three types of cuttings can be considered high. In apical cuttings it was found that the effect of apical dominance, influence some variables, as the number of dormant cuttings, of active buds cuttings, the number of active buds, of leaves, and consequently the number of leaflets. Callus formation was observed in three types of cuttings, however, the basal cuttings presented more tendencies to form adventitious roots. The shoots formed in the basal cuttings were quantitatively higher than the median and apical cuttings. Significant correlations were found to number of active buds cuttings, number of active buds, number of leaflets and the leaf dry mass when correlated with root dry mass. Cuttings removed from the basal portion of the branches of Spondias mombin L. presented better conditions for root development.